Factors Affecting the Tourism Industry and Their Impact on Unemployment, Small and Medium Enterprises, Poverty, and the Human Development Index - Laksono Edhi Lukito Lukito; Wahyu Murti; Yolanda Yolanda; Bambang Bernathos; Rudi Bratamanggala (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The tourism industry is one of the main supporting factors for the economy in Indonesia. The purpose of this study is to analyze and examine the factors that influence the tourism industry and their impact on unemployment, Small and Medium Enterprises, Poverty, and Human Development Index. The research method used an explanatory research study, which aims to test hypotheses about the relationship between variables with ordinary least square, multiple and simple linear regression, statistical descriptive analysis, and classical assumption test. Data processing that used is secondary data, 2005 to 2020 (quarterly), using econometrics Eviews application, 10 version. The results of this study found that foreign tourist visits, rupiah exchange rate, infrastructure, inflation, and tourist destinations had a significant simultaneous effect to the tourism industry. Partially, negative and significant effects on the rupiah exchange rate, and inflation. The tourism industry has negative and significant effect on unemployment and poverty. Furthermore, Small and Medium Enterprises and the Human Development Index has positive and significant effect to tourism industry.